2022
DOI: 10.1108/jadee-05-2022-0092
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural credit and productivity of crops in India: field evidence from small and marginal farmers across social groups

Abstract: PurposeThis work examines the impact of institutional agricultural credit on crop productivity of some major crops such as paddy, cotton, wheat and pulses for small and marginal farmers across various social groups.Design/methodology/approachThe cross-sectional field data on socio economic variables was collected from three Indian states from about 400 small and marginal farmers across various social groups using multi-stage stratified random and purposive sampling through a structured questionnaire by intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Result also found that inefficiency level was significantly high for fifty-fifty input-output share tenant and only output share tenant compared to cash tenant and owner operator implying that Marshallian inefficiency exist due to sharecropping system in the Boro rice production. Yadav & Rao (2022) stated that based on the propensity score matching (PSM) estimation, revealed that average treatment effect (ATE) and average treatment effect on the treated (ATET) for all the selected crops are found to be significantly higher for the treated group vis-à-vis non-treated group suggesting that institutional agricultural credit has a statistically and significant positive impact on the crop productivity. So, it was clear that there is a positive relationship between sharecropping system, informal credit, and productivity.…”
Section: Sharecropping Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Result also found that inefficiency level was significantly high for fifty-fifty input-output share tenant and only output share tenant compared to cash tenant and owner operator implying that Marshallian inefficiency exist due to sharecropping system in the Boro rice production. Yadav & Rao (2022) stated that based on the propensity score matching (PSM) estimation, revealed that average treatment effect (ATE) and average treatment effect on the treated (ATET) for all the selected crops are found to be significantly higher for the treated group vis-à-vis non-treated group suggesting that institutional agricultural credit has a statistically and significant positive impact on the crop productivity. So, it was clear that there is a positive relationship between sharecropping system, informal credit, and productivity.…”
Section: Sharecropping Patternsmentioning
confidence: 99%
“…Studies and research on traditional solar salt businesses explain that financing is a key determinant of the success of solar salt businesses. Financing plays a supportive role in the implementation of agricultural activities, having a crucial impact on funding all farming activities, including both fixed costs and variable costs (Abdallah, 2016;Anang et al, 2016;Yadav & Rao, 2022). Furthermore, this business which is notorious for having high variable costs further emphasizes the importance of financing as a crucial supporting factor to ensure optimal results for solar salt farmers.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of recent studies have been devoted to investigating the effects of agricultural credits on agriculture. While some of these studies used household/farm-level data such as Chandio et al (2017), Ullah et al (2020), Chandio et al (2021), Ma et al (2022), andYadav andRao (2022), some of them identified and addressed linkages using country-level data such as Misra et al (2016), Rehman et al (2017), Anh et al (2020), Seven and Tumen (2020), Manoharan and Varkey (2021), Chandio, Abbas, et al (2022), Chandio, Jiang, et al (2022), and Mahapatra and Jena (2023). The majority of the studies in the first category concluded that agricultural credits help to improve agricultural production efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is the right step, as a similar program has proven empirically effective. Studies in developing countries such as India [ 10 ], Ghana [ 11 ], Pakistan [ 12 ], and Senegal [ 13 ] show identical results, stating that the ability to obtain credit boosts agricultural productivity and technical efficiency. It can help farming households increase their productivity as they can procure more sophisticated technology [ 14 , 15 ] and improve production efficiency as they can procure superior inputs and seeds [ 16 ].…”
Section: Introductionmentioning
confidence: 99%